The Effect of Educational Organizational Commitment as a Moderator Towards Principal Technology Leadership in Curriculum Management ad Teachers' SelfEfficacy - Roslee Talip; Tisebio Anak Tiop (2020)
This study focuses on principal technology leadership in curriculum management, teachers’ selfefficacy and educational organizational commitment. To be specified, this research identify the relationship between principal technology leadership in curriculum management and teachers’ selfefficacy. This is a quantitative research using questionnaire as an instrument and is analysed using SPSS 25.0. Data was collected through a set of adapted questionnaires administered to 306 teachers. Descriptive analysis principal technology leadership in curriculum management, teachers’ self-efficacy and educational organizational commitment being practised at a high level. Pearson correlation test indicated a moderate positive linear relationship for principal technology leadership in curriculum management with teachers’ self-efficacy. Meanwhile, using hierarchical regression is found that administrators need to increase the organizational commitment as it gives the impression of a positive moderator on the relationship between principal technology leadership in curriculum management and teachers’ self-efficacy. The implications and suggestions for further study are also discussed.